Gastroenterological manifestations of COVID-19: first generalizations - Sergey I. Pimanov; Elena A. Dikareva (LLC "MEDIAFORMAT", 2020)
The aim of the work was to review current data on the damage to the gastrointestinal tract and liver in case of COVID-19 infection, its effect on the management of patients with ulcerative colitis, Crohn's disease, and chronic liver diseases during a pandemic. Gastroenterological manifestations in patients with COVID-19 occur in about a quarter of cases and are associated with a severe course of the disease. Liver damage is detected in more than a third (according to many data - in half) of patients and is a predictor of severe infection and an increased risk of death. The main objective of international recommendations is the prevention of COVID-19 disease in patients with inflammatory bowel disease and chronic liver disease. Treatment with large doses of systemic corticosteroids, immunosuppressants and the use of biological therapy increases the risk of severe COVID-19 in case of infection. Patients with liver cirrhosis and coronavirus infection have a high risk of fatal decompensation of the liver disease.